(E)-1-(3-Nitrophenyl)-2-({5-[(1E)-2-(3-nitrophenyl)hydrazin-1-ylidene methyl]-2-thienyl}methylidene)hydrazine - de Lima, G.M.; Harrison, W.T.A.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
The title molecule, C(18)H(14)N(6)O(4)S, adopts a U-shape with the aromatic groups lying syn and oriented in the same direction as the thiophene S atom. Twists away from planarity are evident with the maximum deviation being found for a terminal nitro group: C/C/N/O = 19.0 (3)degrees. The conformation about each of the C=N bonds is E. In the crystal, centrosymmetrically related molecules are connected via N-H center dot center dot center dot O(nitro) hydrogen bonds, forming 14-membered {center dot center dot center dot HNC(3)NO}(2) synthons. These are linked into layers via C-H center dot center dot center dot O(nitro) interactions with the primary interactions between layers being of the type C-H center dot center dot center dot pi, where the pi-system is the thiophene ring.